A kingdom of new cities: Morocco's national Villes Nouvelles strategy. Issue 131 (May 2022) - Côté-Roy, Laurence; Moser, Sarah
Highlights: Morocco is among the most active countries in building new cities from scratch. 19 new cities are underway as part of an ambitious national city-building strategy. We unpack forms of inherent messiness in the 'cohesive' national strategy. We probe the strategy's 'useful fuzziness' and consequences of its ambiguity. We raise problems of accountability, transparency, and incoherence of the strategy. Abstract: Morocco is one of the most active countries in the world in building new cities from scratch. Nineteen new cities are presently underway across the kingdom as part of a national city-building strategy, launched to manage uncontrolled urbanization and to support economic growth. Morocco's city building is illustrative of the global trend in which states are creating urban mega-projects as part of national development strategies, but also reflects the unique local forces shaping new city building in the kingdom. This article provides the first overview of Morocco's new city strategy and projects, which we contextualize within the kingdom's recent extensive urban investments shaped by economic liberalism and persistent state authoritarianism. While new city building in Morocco is driven by the state and presented as a cohesive strategy in official discourse, it is characterized by ambiguity and confusion, introduced through the 'hybrid' role of city-building actors, an undefined policy status, and a lack of coordination among new city projects underway. By critically analyzing the national strategy's forms of ambiguity, we examine the state's modes of speculative interventions that maintain a 'useful fuzziness', raising issues of accountability, transparency, and disconnect in national development visions.